Efficient chimeric mouse production using a novel embryonic stem cell line - G. V. Kontsevaya; N. A. Feofanova; A. G. Menzorov; I. E. Pristyazhnyuk; A. V. Smirnov; N. R. Battulin; L. A. Gerlinskaya (Вавиловский журнал генетики и селекции)
Embryonic stem cells are commonly used for generation of transgenic mice. Embryonic stem cells could participate in the development of chimeric animals after injection into a blastocyst. Injection of genetically modified embryonic stem cells could lead to germ line transmission of a transgene or genomic modification in chimeric mice. Such founders are used to produce transgenic lines of mice. There are several projects dedicated to production of knock-out mouse lines (KOMP Repository, EUCOMM, Lexicon Genetics). Never-theless, there is a need for complex genome modifications, such as large deletions, reporter genes insertion into the 3’ gene regulatory sequence, or site-specific modifications of the genome. To do that, researchers need an embryonic stem cell line that is able to participate in chimeric animal formation even after prolonged culture in vitro. Several lines of mouse embryonic stem cells were produced in the Laboratory of Developmental Genetics of the Institute of Cytology and Genetics SB RAS. We tested DGES1 cell line (2n = 40, XY) (129S2/SvPasCrl genetic background) for chimeric mice production at the Center for Genetic Resources of Laboratory Animals at ICG SB RAS. Embryonic stem cells were injected into 136 blastocysts (B6D2F1 genetic background), which were transplanted into CD-1 mice. Among 66 progeny, 15 were chimeric, 4 of which were more than 80 % chimeric judged by coat color. All chimeras were males without developmental abnormalities. 10 of 15 males were fertile. Microsatellite analysis of the progeny of chimeric mice revealed embryonic stem cell line DGES1 contribution to the gamete formation. Thus, a novel DGES1 embryonic stem cell line could be efficiently used for transgenic mouse production using B6D2F1 blastocysts and CD-1 recipients.